Sox9 regulates self‐renewal and tumorigenicity by promoting symmetrical cell division of cancer stem cells in hepatocellular carcinoma. Issue 1 (25th March 2016) - Liu, Chungang; Liu, Limei; Chen, Xuejiao; Cheng, Jiamin; Zhang, Heng; Shen, Junjie; Shan, Juanjuan; Xu, Yanmin; Yang, Zhi; Lai, Maode; Qian, Cheng
Abstract : Hepatocellular carcinoma (HCC) is a highly aggressive liver tumor containing cancer stem cells (CSCs) that participate in tumor propagation, resistance to conventional therapy, and promotion of tumor recurrence, causing poor patient outcomes. The protein SRY (sex determining region Y)‐box 9 (Sox9) is a transcription factor expressed in some solid tumors, including HCC. However, the molecular mechanisms underlying Sox9 function in liver CSCs remain unclear. Here, we show that Sox9 is highly expressed in liver CSCs and that high levels of Sox9 predict a decreased probability of survival in HCC patients. We demonstrate that Sox9 is required for maintaining proliferation, self‐renewal, and tumorigenicity in liver CSCs. Overexpression of exogenous Sox9 in liver non‐CSCs restored self‐renewal capacity. Additionally, a reduction in the asymmetrical cell division of spheroid‐cultured liver CSCs was observed when compared with differentiated cancer cells or liver CSCs with inhibited Notch signaling. Furthermore, we demonstrate that Sox9 is responsible for the asymmetrical‐to‐symmetrical cell division switch in liver CSCs. Sox9 also negatively regulates Numb expression, contributing to a feedback circuit that maintains Notch activity and directs symmetrical cell division. Clinical analyses revealed that the Sox9 High Numb Low profile is associated with poor prognosis in human HCC patients. Conclusion: We demonstrate that Sox9 plays a critical role in self‐renewal and tumor propagation of liver CSCs and identify the molecular mechanisms regulated by Sox9 that link tumor initiation and cell division . (Hepatology 2016;64:117–129)